Aldo-keto reductase (AKR) superfamily: Genomics and annotation - Mindnich, Rebekka D.; Penning, Trevor M. (Human genomics, 2009)
Aldo-keto reductases ( AKRs ) are phase I metabolising enzymes that catalyse the reduced nicotinamide adenine dinucleotide (phosphate) (NAD(P)H)-dependent reduction of carbonyl groups to yield primary and secondary alcohols on a wide range of substrates, including aliphatic and aromatic aldehydes and ketones, ketoprostaglan-dins, ketosteroids and xenobiotics. In so doing they functionalise the carbonyl group for conjugation (phase II enzyme reactions). Although functionally diverse, AKRs form a protein superfamily based on their high sequence identity and common protein fold, the (α/(β) 8 -barrel structure. Well over 150 AKR enzymes, from diverse organisms, have been annotated so far and given systematic names according to a nomenclature that is based on multiple protein sequence alignment and degree of identity. Annotation of non-vertebrate AKRs at the National Center for Biotechnology Information or Vertebrate Genome Annotation (vega) database does not often include the systematic nomenclature name, so the most comprehensive overview of all annotated AKRs is found on the AKR website ( http://www.med.upenn.edu/akr/ ). This site also hosts links to more detailed and specialised information (eg on crystal structures, gene expression and single nucleotide polymorphisms [SNPs]). The protein-based AKR nomenclature allows unambiguous identification of a given enzyme but does not reflect the wealth of genomic and transcriptomic variation that exists in the various databases. In this context, identification of putative new AKRs and their distinction from pseudogenes are challenging. This review provides a short summary of the characteristic features of AKR biochemistry and structure that have been reviewed in great detail elsewhere, and focuses mainly on nomenclature and database entries of human AKRs that so far have not been subject to systematic annotation. Recent developments in the annotation of SNP and transcript variance in AKRs are also summarised.